Enhanced room temperature energy storage density of Bi(Li1/3Ti2/3)O3 substituted Bi0.5Na0.5TiO3–BaTiO3 ceramics. (27th April 2021) - Karakaya, Merve; Adem, Umut
Abstract: For high power electronics applications, relaxor ferroelectrics are promising materials due to their superior energy storage properties. In this study, we investigate the energy storage properties of novel lead free relaxor ferroelectric ceramics (1− x )(0.92Bi0.5 Na0.5 TiO3 –0.08BaTiO3 )– x Bi(Li1/3 Ti2/3 )O3 (abbreviated as BNT–8BT– x BLT). BNT–8BT composition which is close to morphotropic phase boundary was chosen as the base due to its large maximum polarization ( P m ) and higher ratio of weakly polar tetragonal phase which is expected to facilitate ergodic relaxor behavior and improve energy storage density. The substitution of BLT to the BNT–8BT strongly disrupts the correlations between the polar nanoregions and the transition from nonergodic to ergodic relaxor state occurs already at x = 0.02 BLT at room temperature. Largest energy density ( W rec ) at 61 kV cm −1 was obtained for x = 0.02 sample (0.656 J cm −3 ), followed by x = 0.03 ( W rec = 0.614 J cm −3 ) and x = 0.05 ( W rec = 0.559 J cm −3 ). The x = 0.02 sample keeps its energy storage density at high temperatures (i.e. W rec = 0.88 J cm −3, η = 97%, E m = 65 kV cm −1 at 125 °C), while larger electric field (up to 89 kV cm −1 ) could be applied to the x = 0.05 sample with the smallest grain size and energy density of 1.03 J cm −3 was reached at room temperature. Energy storage density values of BLT substituted materials normalized per unit applied electric field are promising among BNT-based materials.